The genus Nyctiophylax Brauer in China (Trichoptera, Polycentropodidae) - Zhong, Hua; Yang, Lian-Fang; Morse, John C. (Zootaxa, 2014)
Currently, 8 species of the genus Nyctiophylax Brauer are known from China. Examination of material collected from Guangdong, Guangxi, Jiangxi and Sichuan Provinces during 2004–2005 has revealed 4 new species and 2 new records of this genus, bringing the number of Chinese Nyctiophylax species to 14. Newly described species include: Nyctiophylax (Paranyctiophylax) crinalis n. sp., N. (P.) dactylatus n. sp., N. (P.) orbicularis n. sp., and N. (P.) macrorrhinus n. sp. Nyctiophylax (Paranyctiophylax) sagax Mey and N. (N.) amphonion Malicky & Chantaramongkol are newly recorded for the Chinese fauna, which are re-illustrated and re-described for clear comparisons. The additional collection sites for the previously described species are provided.